Contribution of human capital accumulation to Canadian economic growth - Audra J. Bowlus; Youngmin Park; Chris Robinson (Bank of Canada, 2022)
This paper quantifies the contribution of human capital accumulation to the growth of real gross domestic product (GDP) in Canada. GDP growth is decomposed into contributions from physical capital, hours worked, human capital supplied per hour and total factor productivity. Using a "flat spot" identification strategy, we separately estimate the price and quantity of human capital using wage data from the Labour Force Survey. We find that growth in human capital supplied per hour explains around one-fifth of GDP growth and two-thirds of the Solow residual over the period from 1997 to 2018. While growth in hours worked is expected to slow down in the near future, human capital supplied per hour is expected to continue to be an important driver of GDP growth.
Keywords: D24; E24; J24; J31; O47; 330; Econometric and statistical methods; Labour markets; Potential output; Productivity